Studies on the Effect of Purging the Freshwater Prawn Macrobrahium Rosenbergii in Extending its Iced storage life - Sudhir B (Department of Processing Technology, College of Fisheries, 1995)
In this study the effect of purging the prawn Macrobrachiumrosenbergiito improve its quality during iced storage was studied. Various biochemical and sensory changes that occurred during iced storage was observed. Experiments were done both for headless and headon prawns. For the headless prawns the treatments were (1) freshwater purged, and (2) purged and further chlorine dipped and the purging time was 5 hrs in a 500 litre tank. For the headon prawns purging in running water in a 5000 litre tank for 18 hrs was done. Both experiments were done with a control of unpurged prawns. The headless prawns kept longer than the head on product style more so perhaps due to the effect of beheading. Analysis of variance for alpha amino nitrogen, TVB, NPN, pH and sensory evaluation showed significant difference between purged and unpurged samples in the headon product sytle, the purged sample being of better quality. Similar results were not evident in the case of headless scampi. Longer duration of purging for 18 hrs or longer seems to have an influence on quality. For the headon prawns the acid insoluble ash showed a significant difference between treatments indicating the success in flushing the gut contents by purging. Sensory evaluation showed that headless and headon prawns were acceptable for more than 10 and 7 days respectively. Mushiness was not observed in the headless prawns but started from the third day for the headon control and the fifth day for the purged prawn. In headon prawn presence of black vein was reduced considerably by purging. Thus it was seen that there was an improvement in the general quality of the prawn due to purging.